Avaliação do perfil clínico-patológico e desfecho do câncer de mama em uma microrregião de saúde – MG: uma coorte retrospectiva - Haddad, Cássio Furtini (2023)
Breast cancer represents the most frequent type of cancer and the main cause of cancer death in women, constituting a heterogeneous disease, with high incidence, prevalence and morbi-mortality. The disease, when diagnosed and treated in a timely manner, has a good prognosis. Thus, survival is closely linked to the biological characteristics of the tumor, disease staging, diagnosis and therapy used. Objective: to investigate the clinicopathological profile and outcome of women with breast cancer diagnostic who follow the doctor at a specialized health care center in a microregion in the south of the state of Minas Gerais. Methodology: data from medical records of 300 patients were analyzed. Clinical, pathological variables and outcomes were collected using a structured form. Quantitative and comparative analyzes were performed between the groups studied. Results: 35.2% of the patients were under 50 years of age at the time of diagnosis; premenopausal patients accounted for 38.9% of the cases; and 14.1% of them had a positive family history for breast cancer. The diagnosis was made by alteration in the clinical examination in 75.8% of the cases. The mean tumor size was 28.7 mm (± 19,4). There was a higher prevalence of the luminal molecular subtype (82.1%), while HER-2 tumors represented 6.7% of cases and triple-negative tumors, 11.2%. The most frequent stages were IIA and IA, 29.1% and 24.3% of the total cases, respectively. Stage 0 represented only 6.4% of patients. The mean time between the medical consultation and the histological diagnosis and between the histological diagnosis and the beginning of treatment was 63.2 days (± 48,1) and 39.6 days (± 29,8), respectively. Most of the patients underwent conservative surgery (81.2%), adjuvant radiotherapy (88.8%), chemotherapy (70.8%) and hormonetherapy (78.1%). During the analysis period, most patients (87.3%) did not have disease recurrence. No significant differences were found in the risk of death or in the risk of recurrence as a function of age at diagnosis. The increased stage at diagnosis was related to a higher risk of death (p = 0.045), while the risk of recurrence was related to a higher stage and larger tumor size (p = 0.001 and p = 0.018, respectively). Conclusions: a significant rate of breast cancer cases was observed in patients under 50 years of age. Age did not correlate with risk of death, risk of recurrence, survival time and time to recurrence, however, recognized prognostic factors such as stage at diagnosis, tumor size, histological grade and Ki67 were variables associated with outcomes. Average time interval for establishing the histological diagnosis was greater than 60 days.